1999
DOI: 10.1046/j.1365-2249.1999.00766.x
|View full text |Cite
|
Sign up to set email alerts
|

Th1 (IL-2, interferon-gamma (IFN-γ)) and Th2 (IL-10, IL-4) cytokine production by peripheral blood mononuclear cells (PBMC) from patients with systemic lupus erythematosus (SLE)

Abstract: We investigated the production of IL‐2, IFN‐γ, IL‐10 and IL‐4 by PBMC from 24 patients with SLE and 10 healthy individuals. Basal and mitogen‐stimulated (lipopolysaccharide and phytohaemagglutinin (LPS + PHA)) cytokine production was determined in a whole blood assay (WBA). Supernatants were collected and assayed with specific ELISAs. Although the IL‐2 and IFN‐γ contents did not differ significantly between patients and controls under both conditions, statistically significant correlations were found between e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
138
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(147 citation statements)
references
References 51 publications
7
138
2
Order By: Relevance
“…IFN-γ is a key cytokine that controls Th1-dependent immune responses. Concentrations of IFN-γ are increased in SLE patients, and the production of IFN-γ by PBMCs from SLE patients is significantly correlated with global disease activity [13,29]. In the present study, we observed an increase of IFN-γ in SLE patients compared with normal and disease controls, but negative correlation with C3 and C4.…”
Section: Discussionsupporting
confidence: 53%
“…IFN-γ is a key cytokine that controls Th1-dependent immune responses. Concentrations of IFN-γ are increased in SLE patients, and the production of IFN-γ by PBMCs from SLE patients is significantly correlated with global disease activity [13,29]. In the present study, we observed an increase of IFN-γ in SLE patients compared with normal and disease controls, but negative correlation with C3 and C4.…”
Section: Discussionsupporting
confidence: 53%
“…The IFN-g serum concentrations and its production by PBMC were found in some studies to be increased (28,29), unchanged (23,30) and decreased (31,32). In this study, serum IFN-g levels in SLE patients were not significantly different neither from those of healthy controls nor LV patients.…”
Section: Discussioncontrasting
confidence: 58%
“…The serum levels of this cytokine, to our knowledge, have not been reported. However, its production by PBMC was reported to be increased in CD8(±) cells (31,34), unchanged (30) or decreased (29) in SLE , compared to control PBMC derived from healthy subjects. In this report, IL-4 basal production by PBMC derived from SLE patients was slightly, but significantly, increased in comparison with that of control cells.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 In particular, a switch from a type I to a type II T-helper has been demonstrated, where the serum levels of the Th-2 cytokines such as interleukin IL-4, IL-6 and IL-10 are elevated, while there is an observed decrease in the production of Th-1 cytokines including IL-1, IL-2 and interferon IFN-g. 1,21,22 Among these cytokines, IL-10 seems to play a central role in the pathogenesis of SLE as well as in disease flare induction. 1 IL-10 is an important immunoregulatory cytokine that inhibits T-cell function, inhibits antigen-presenting cells and promotes B-cell-mediated functions.…”
Section: Ingenuity Pathway Analysismentioning
confidence: 99%